Effectiveness of Percutaneous Drainage on the Treatment of Mesh-Induced Seroma - Öner, Serkan; Altay, Çetin Murat (European Journal of Therapeutics, 2023)
Objective: To investigate the effectiveness of percutaneous treatment of mesh-related seroma to salvage the mesh. Methods: Between October 2015 and December 2017, a total of four patients [three females, one male; mean age, 68.5±22 years (range, 61–83 years)] with repaired ventral hernia who underwent percutaneous drainage for the treatment of peri-mesh seromawere evaluated, retrospectively. In all patients, ultrasound was used to diagnose seroma and was the guiding imaging method during percutaneous procedures. General purpose pigtail-percutaneous drainage sets were used in all patients. Ethanol (96%) was used for sclerotherapy, and a fibrinolytic agent was used to destroy septa in multilocular collections. Laboratory investigations and comorbidities were evaluated in hospital data service, retrospectively. Mainly, the clinical success rates were evaluated, and technical success rates and procedure-related morbidity and mortality were also evaluated. Results: A total of 11 percutaneous drainage sessions (median, 2; range 1–6) were performed in four patients. The mean volume of fluid collections was 807.3±3006 cc (median, 291 cc; range, 114–3120 cc). There was no significant difference between the mesh sizes. A technical success rate was 100%. There was no procedure-related morbidity and mortality. The mean of the recurrence time of the peri-mesh seroma was 3.5±11 months (median, 2 months; range, 1–12 months). In all patients, during the follow-up, seroma was accumulated repetitively. Conclusion: Percutaneous treatment is an effective management option to salvage the mesh in patients with mesh-related seroma who are poor surgical candidates or whose mesh cannot be removed.